Why Do Children Love Electricity? Multivariate Evidence from Hands-On Electronics Learning in Elementary STEM Education - Rijanto, Tri; Yudha, Rivo Panji (ISEJ : Indonesian Science Education Journal, 2026)
The integration of hands-on learning into elementary science education has garnered increasing scholarly attention, yet empirical investigations examining its simultaneous effects on multiple educational outcomes remain limited, particularly within the domain of electricity learning at the primary school level. This study examined the effects of a structured hands-on electronics learning program on elementary students' scientific curiosity, STEM interest, problem-solving skills, and scientific engagement using a multivariate analytical framework. Employing a quasi-experimental pretest–posttest nonequivalent control group design, 300 Grade 4–6 students (aged 9–12 years) from Lakarsantri District, Surabaya, Indonesia, were assigned to either a hands-on electronics intervention (n = 150) or conventional science instruction (n = 150). The eight-session intervention engaged students in circuit building, conductor investigations, and collaborative mini-project design using modular electronics kits, facilitated through the 5E instructional model. Data were collected using validated instruments measuring all four outcome constructs and analyzed via Multivariate Analysis of Covariance (MANCOVA), with prior academic achievement and digital literacy serving as covariates. Results revealed a statistically significant and large omnibus multivariate effect (Wilks' Λ = .312, F(8, 586) = 41.73, p < .001, η²p = .363), with significant univariate effects across all four dependent variables (η²p range: .356–.427). Discriminant function analysis further identified STEM interest and curiosity as the primary dimensions differentiating the two groups (classification accuracy = 89.3%). These findings demonstrate that hands-on electronics learning constitutes a pedagogically powerful approach for cultivating multidimensional STEM competencies in elementary education, with significant implications for curriculum design, teacher professional development, and early STEM engagement policy.